A clinicopathological study of sinonasal lesions-5 years study in a rural hospital setup - Savita Dongapure; Anand Anantharao Shankar; Raja Parthibhan (Journal of Pathology of Nepal)
Background: Sinonasal lesions of both non-neoplastic and neoplastic variants are frequently observed by clinicians in the nasal cavity and paranasal sinuses. Sinonasal lesions are important due to divergence in their behavior and prognosis. Hence, a careful histological workup remains the mainstay of a final definitive diagnosis and timely intervention.